2021
DOI: 10.3390/ijerph182010590
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Psychosocial Resilience Resources in Obese Pregnant Women with Threatened Preterm Labor—A Cross-Sectional Study

Abstract: Background: The purpose of the study was to assess the level of such psychosocial resilience resources as self-efficacy, dispositional optimism, and health locus of control in pregnant women with obesity with threatened premature labor. Methods: The study was performed in the years 2017–2020 in a group of 328 pregnant women hospitalized due to threatened preterm labor and diagnosed with obesity before the pregnancy. The following instruments were applied: the Life Orientation Test, the Generalized Self-Efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…A study conducted by Mahmoodabad et al among pregnant Iranian women with a normal course of pregnancy found that the overall self-efficacy score was 23.31, lower than in our study [ 29 ]. Values similar to those obtained in our own study were achieved in primiparous women in the third trimester of pregnancy (28.29) [ 30 ], in obese pregnant women with threatened preterm labor (28.02) [ 31 ], in pregnant patients with hyperglycemia (31.58) [ 25 ] and in women after miscarriage (30.29) [ 32 ]. The regression analysis of our study showed that the explanatory variables for self-efficacy were age, wealth, and planning a pregnancy, which may be due to the fact that older women with higher socioeconomic status and those planning a pregnancy were more aware of pregnancy and the need to take care of their own health and that of their unborn child.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…A study conducted by Mahmoodabad et al among pregnant Iranian women with a normal course of pregnancy found that the overall self-efficacy score was 23.31, lower than in our study [ 29 ]. Values similar to those obtained in our own study were achieved in primiparous women in the third trimester of pregnancy (28.29) [ 30 ], in obese pregnant women with threatened preterm labor (28.02) [ 31 ], in pregnant patients with hyperglycemia (31.58) [ 25 ] and in women after miscarriage (30.29) [ 32 ]. The regression analysis of our study showed that the explanatory variables for self-efficacy were age, wealth, and planning a pregnancy, which may be due to the fact that older women with higher socioeconomic status and those planning a pregnancy were more aware of pregnancy and the need to take care of their own health and that of their unborn child.…”
Section: Discussionsupporting
confidence: 83%
“…There are few scientific reports in the literature addressing the issues of acceptance of illness and psychosocial resilience resources of pregnant women: self-efficacy and health locus of control and their determinants, especially in the case of the occurrence of diseases complicating pregnancy, which is important in the care of women with abnormal pregnancy [ 25 , 29 , 30 , 31 , 32 , 42 , 43 ]. The implemented care should be based on the real needs, capabilities, and expectations of pregnant women to cope with the situation.…”
Section: Discussionmentioning
confidence: 99%
“…The present findings add to those from our previous study that analyzed self-efficacy, life orientation, and health locus of control in pregnant women diagnosed with threatened premature labor [46]. One limitation of the present study is the lack of a detailed analysis of personal resources in women hospitalized due to high-risk pregnancy at a point before the complication had occurred and after the completion of pregnancy.…”
Section: Discussionmentioning
confidence: 54%
“…To summarize, resilience, as an intermediary, can affect both maternal pregnancy stress and maternal prenatal anxiety, as a protective factor against both (43). The higher the level of resilience of pregnant women, the lower the pregnancy pressure and the milder the symptoms of prenatal anxiety (44).…”
Section: Discussionmentioning
confidence: 99%